Adaptation actions to climate change in African agriculture: Effectiveness and challenges - Tadesse, Getaw; Barry, Ndeye Yacine (AKADEMIYA2063, 2024)
Climate change poses a significant burden to African development and economic growth, impacting households at both national and regional levels. While accounting for only 3–4 percent of global emissions, Africa is most vulnerable to climate change due to low levels of socioeconomic growth (Kikstra et al. 2022). Africa’s vulnerability to climate change is exacerbated by its reliance on rain-fed agriculture, environmental degradation, inadequate infrastructure, widespread poverty, and increased frequency and intensity of climate-related disasters. These factors make Africa highly susceptible to climate-related disruptions such as droughts and floods and can amplify the impact of climate-related disasters on communities, economies, and ecosystems (UNECA 2013; WMO 2020). Effective adaptation strategies and risk financing mechanisms are crucial for building regional adaptive capacity and resilience.